Education on Family Law and the Division of Marital Property: A Comparative Study of Couples With and Without Prenuptial Agreements at the Mungkid Religious Court, Magelang Regency - Akhmad Sholih Uddin; Husna Nashihin (International Journal of Post Axial: Futuristic Teaching and Learning, 2025)
This study is motivated by the high divorce rate in Indonesia and the complexity of resolving joint property disputes arising after divorce. The primary objective is to compare the methods of resolving joint property division cases with and without prenuptial agreements at the Mungkid Religious Court, Magelang Regency. The research method used is descriptive qualitative with a field case study approach. Primary data were collected through observation, documentation, and interviews with court officials. The results conclude that joint property cases without a prenuptial agreement are resolved through litigation, applying a 50:50 equal division based on the Marriage Law and KHI, although judges hold discretion for proportional division based on jurisprudence. Conversely, the existence of a prenuptial agreement empirically succeeds in diverting joint property disputes directly to non-litigation channels (deliberation) effectively and swiftly, thereby accelerating the main divorce proceedings without cumulative conflicts.